The Jurisprudence Hadith Analysis of Bribery and It's Impact on Human Life - Nuryamin Nuryamin (UIN Sunan Gunung Djati Bandung, 2018)
This article discusses the concept of bribery in the perspective of hadith jurisprudence and its impact on human life. By looking at some definitions of bribery, it is found that all definitions give different meanings, goals, and aspects, there are essence of bribery, or which have similarities to them (such as gratification), because bribery is a social phenomenon and has many patterns making it difficult to define definitions the right and limit the meaning. But a definition that explains the meaning of bribery objectively, namely: Giving given to someone (an official) so that the right becomes wrong and wrong becomes right, because it summarizes the essence of bribery practice and is considered a comprehensive definition of all banned aspects of bribery, so let us choose this. In Qur’ān and Ḥadīth, Allah forbade his servant to eat bribery property, because this property was included as part of consuming other people's assets with vanity. Even though bribery is called a variety of terms in daily life, such as facilitation payments, tips, etc., the legal status and prohibition cannot change with these various terms. Bribes also have the potential to create hate conflicts and hostility among members of the community. Because in essence, bribery is only a tool for those who hold policies to oppress the weak. On the other hand, those who surrendered their wealth to the recipients of this bribe gave their assets very forcefully.